A multi-scale computational assessment of channel gating assumptions within the Meissner corpuscle - Djordje Peric (Journal of Biomechanics, 2015)
From the macroscopic mechanical deformation of skin to the feeling of touch is a chain of complex events whereby information is converted from one form to another between different scales. An important link in this chain is receptor activation, which requires incorporation of microanatomical, cellular and ion channel transduction models. Of particular interest is the deformations at the axon membrane bi-layer, which are believed to be involved in mechanoelectrical signal transduction by activation of ion channels. We present a fully coupled multi-scale finite element analysis of the finger pad during tactile exploration, whereby the Meissner corpuscle, which is modeled as a single representative volume element (RVE) at the microscopic level, interacts with the macroscopic finger model. Maximum values of local stretching and compression occurring at the bi-layer are monitored for finger models with and without fingerprints, the presence of which generates a remarkable amplification of the signal. The contours of the surface being explored are well represented by the maximal peaks observed within the membrane.